A Writing Life Revisiting the Past - Weintraub, Stanley, 1929-2019; Pharand, Michel W.; Weintraub, David, 1949-; Project Muse; Project Muse. (Project Muse, 2020)
In A Writing Life, Stanley Weintraub applies the biographical skills he perfected over a lifetime of writing to tell his own story. In doing so, he introduces us to a who's who of the twentieth century whom he encountered in his life and in his research, from Eddie Fisher to C. P. Snow, from Leonard Woolf to Pierre Salinger, from Ray Bradbury to Danny Kaye to Isaac Bashevis Singer, and he takes us inside his world of discovery and enables us to feel his passion and experience his relentless intensity for finding the letters, diaries and documents that reveal the important details of history. Weintraub was one of the preeminent biographers, one of the most distinguished military historians, and one of the most important scholars of playwright George Bernard Shaw of the last 60 years. He published biographies of American and English figures of political, cultural and military significance, including Shaw, Lawrence of Arabia, Whistler, Beardsley, Queen Victoria (which reached #1 on The Times of London bestseller list), Prince Albert, King Edward VII, Disraeli, MacArthur, Eisenhower, Marshall and FDR; he wrote histories covering aspects of the American Revolution, the Civil War, World War I, the Spanish Civil War, World War II, and the Korean War, and he wrote a series of books about wartime Christmases, including Washington getting home for Christmas in 1783, Sherman reaching Savannah for Christmas in 1864, the Christmas Truce of 1914, Christmas at the Battle of the Bulge in 1944, and a military escape from Korea at Christmas in 1950.
Preface I. Making the most of possibilities -- Preface II. Acquiring a name -- A kid's war I : beginnings, 1929-1941 -- A kid's war Ii : the real thing, 1941-1945 -- Kid to khaki, 1946-1951 -- Korea, 1951-1953 -- War in the wards, 1952-1953 -- Golden gates, 1953-1956 -- Beginning again, 1956-1965 -- Beardsley and beyond, 1966-1968 -- The Whistler decade, 1969-1977 -- Victoria and its successors -- Victorian sunset -- Pearl Harbor and after -- Victorian aftermath -- Farewell, Victoria! -- Wartime Christmases -- American wars -- Afterword. Tributes to Stanley Weintraub by fellow Bernard Shaw scholars.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
"OED citations by Stanley Weintraub": pages xviii-xxi.
"Books by Stanley Weintraub": pages xiv-xvii.
Description based on print version record.
Keywords: Shaw, Bernard, -- 1856-1950 -- Criticism and interpretation -- History; Weintraub, Stanley, -- 1929-2019.; Literary historians -- United States -- Biography; Military historians -- United States -- Biography; Historians -- United States -- Biography; Biographers -- United States -- Biography; Electronic books; Biography; Electronic books